On the Extrapolation of Entire Functions Observed in a Gaussian White Noise - Ibrcigimov, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We solve the problem of extrapolation of an analytic function of a certain class in the case where its values are observed in a white noise whose intensity is not high.